2019
DOI: 10.1038/s41598-019-51589-9
|View full text |Cite
|
Sign up to set email alerts
|

Artificial spinning of natural silk threads

Abstract: Silk producing arthropods spin solid fibres from an aqueous protein feedstock apparently relying on the complex structure of the silk protein and its controlled aggregation by shear forces, alongside biochemical changes. This flow-induced phase-transition of the stored native silk molecules is irreversible, environmentally sound and remarkably energy efficient. The process seemingly relies on a self-assembling, fibrillation process. Here we test this hypothesis by biomimetically spinning a native-based silk fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…From our description above it follows that the pocket volume (as determined from SEM images) corresponds to phase-separated water. This is supported by evidence that upon exiting the spinneret natural silk fibres retain a considerable amount of water (~70%) which is mostly lost while it is drawn through the air 43 , 46 , 47 . Hence we can plot the dehydration process versus structure development as shown in Fig.…”
Section: Resultsmentioning
confidence: 75%
“…From our description above it follows that the pocket volume (as determined from SEM images) corresponds to phase-separated water. This is supported by evidence that upon exiting the spinneret natural silk fibres retain a considerable amount of water (~70%) which is mostly lost while it is drawn through the air 43 , 46 , 47 . Hence we can plot the dehydration process versus structure development as shown in Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Researchers have been trying to recreate the properties of spider silk through artificial spinning for several decades now, with mixed success, [ 9 , 46 , 47 , 48 ]. In the comprehensive review by Koeppel et al [ 49 ], the authors relayed that the general consensus across the field is that the excellent properties of many artificial silk fibres are mainly derived from a stretch-induced orientation of the fibrils, the high crystalline fraction of the material, and effective fibril linking (through the use of high molecular weight proteins).…”
Section: Designing Biomimetic Fibresmentioning
confidence: 99%
“…In fact, it has been reported that shear can induce protein aggregation, 36,37 and this effect is particularly prominent with silk-based proteins. 38 Both the spider and silkworm are capable of pulling and extruding (respectively) liquid protein from their glands and through the use of shear, a phase transition occurs which aggregates the protein into its well-known solid form. However, in the context of drug delivery, it would be particularly interesting to be able to utilise this and form capsules where the outer shell has aggregated and is solid, but internally there is still a liquid phase, i.e.…”
Section: Resultsmentioning
confidence: 99%